Does the use of topical anesthetics reduce the perception of pain during needle puncture and anesthetic infiltration? Systematic review and meta-analysis of randomized controlled trials - Maia, F. P.A.; Araujo Lemos, C. A.; de Souza Andrade, E. S.; de Morais, S. L.D.; do Egito Vasconcelos, B. C.; Pellizzer, E. P. [UNESP] (Elsevier, 2022)
The objective of this systematic review was to assess whether the use of topical anesthetics reduces the perception of pain during puncture and anesthetic infiltration. Twenty-two randomized controlled clinical trials, published in English on or before August 6, 2020, were found in the PubMed/MEDLINE, Scopus, and Cochrane Library databases. Risk of bias was determined for randomization and other issues. A total of 1029 patients were evaluated using parameters such as type of topical anesthetic, application site, and pain (measured on a scale). Some studies assessed more than one topical anesthetic. Seventeen of them showed a reduction in pain from needle puncture and four from infiltration. Meta-analyses for some results showed considerable statistical heterogeneity. Regarding pain during needle puncture of the maxilla, statistically significant differences were observed in the topical anesthetics group, in both the vestibular (P = 0.0002) and palatal (P = 0.005) region. This was different from the mandible, for which there was no statistically significant difference (P = 0.07). With regard to pain caused by anesthetic infiltration in the maxilla, there was no difference in the use of anesthetic in relation to the control group (P = 0.11). Given these findings, using topical anesthetics only relieves pain during needle puncture and in the maxilla. PROSPERO 2020: CRD42020206362.
Keywords: dental anesthesia; local anesthesia; mouth mucosa; needles; nerve block; pain